Advertising archetypes' impact on physician engagement and behavior in the context of healthcare products - Woodside, Arch; Persing, A.; Ward, B.; Decotiis, A. (John Wiley & Sons, 2018)
The pharmaceutical industry spends billions annually on marketing to physicians (over $4.3 billion in 2014). The industry as a whole has a lot of experience in determining what to say to physicians, but it is less confident when it comes to how to say it-sometimes leading to advertising that does not engage, thereby costing sales. In an effort to define a set of rule-based guidelines for effective pharma branding, the study adapts the primary Jungian archetypes to develop the first collection of archetypal tones of voice for healthcare products. The study here demonstrates, via a series of fuzzy-set qualitative comparative analyses that well executed ads following an archetype consistently connect with physician audiences, while nonarchetypal healthcare ads demonstrate an inconsistent performance. Such an analysis would traditionally take the form of null hypothesis significance testing (NHST), but NHST provides substantially less insights than algorithm modeling and the use of fuzzy-set qualitative comparative analysis as this study describes.